The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/med.21565
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of resveratrol: Evidence from clinical studies

Abstract: Resveratrol is a polyphenolic nutraceutical that exhibits pleiotropic activities in human subjects. The efficacy, safety, and pharmacokinetics of resveratrol have been documented in over 244 clinical trials, with an additional 27 clinical trials currently ongoing. Resveretrol is reported to potentially improve the therapeutic outcome in patients suffering from diabetes mellitus, obesity, colorectal cancer, breast cancer, multiple myeloma, metabolic syndrome, hypertension, Alzheimer's disease, stroke, cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
238
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(277 citation statements)
references
References 258 publications
1
238
0
8
Order By: Relevance
“…A search of the clinical trials database (http://clinicaltrials.gov/) revealed that there are a total of 244 human clinical trials utilizing RE. These clinical trials investigated the potential beneficial effects of RE in the management of diabetes mellitus, obesity, Alzheimer's disease, dyslipidemia, hypertension, stroke, cardiovascular diseases, kidney diseases, pulmonary diseases, eye diseases, rhinopharyngitis, inflammatory diseases, metabolic syndromes, and cancers [137]. RE was documented to exhibit adverse effects in most of these trials.…”
Section: Resveratrol Interacts With and Attenuates The Action Of Othementioning
confidence: 99%
“…A search of the clinical trials database (http://clinicaltrials.gov/) revealed that there are a total of 244 human clinical trials utilizing RE. These clinical trials investigated the potential beneficial effects of RE in the management of diabetes mellitus, obesity, Alzheimer's disease, dyslipidemia, hypertension, stroke, cardiovascular diseases, kidney diseases, pulmonary diseases, eye diseases, rhinopharyngitis, inflammatory diseases, metabolic syndromes, and cancers [137]. RE was documented to exhibit adverse effects in most of these trials.…”
Section: Resveratrol Interacts With and Attenuates The Action Of Othementioning
confidence: 99%
“…Anti-obesity activity of resveratrol has been reported in laboratory animal models, including mice [89], rats [90], primates [91], and humans [92]. The attributed pathways occur in the WAT and include adipogenesis, lipolysis, and lipogenesis [93].…”
Section: Possible Beneficial Mechanisms Of Maternal Resveratrol Adminmentioning
confidence: 99%
“…By activating sirtuin 1 (SIRT1), one of the SIRT family of deacetylases which are claimed to act as longevity regulators, resveratrol is considered to be a potent anti‐aging agent. Over the years, as reported by many basic science investigations and over 240 clinical trials, resveratrol exerts beneficial effects against chronic diseases, including cardiovascular diseases (CVDs), diabetes mellitus, hypertension, Alzheimer's disease, liver diseases and kidney diseases, and carcinomas, such as breast cancer, colorectal cancer, and myeloma (Singh et al, ). Among these disorders, aging is likely to be the most common risk factor.…”
Section: Introductionmentioning
confidence: 99%